Development and Validation of a Short Version Sport Orientation Questionnaire for Chinese Adolescents (SOQ-CA) - Chang, Jindong; Yi, Yali; Song, Naiqing (Frontiers in Psychology, 2020)
With a noted decrease in adolescent physical activity in the past decade, resulting in health risks is increasing. Sport orientation correlates closely with physical activity. A sufficient assessment scale that measures an individual’s sport orientation is important to measure an adolescent’s physical inactivity. The purpose of this study was to develop and validate a short version of the sport orientation questionnaire for Chinese adolescents (SOQ-CA). Based on Gill’s SOQ and previous literature, an initial 30-item questionnaire was developed to create the original SOQ-CA. A five-point Likert scale was used to measure by self-report. In this study, three surveys were conducted. Volunteer participants completed 1,235 valid questionnaires. The data of the first collection sample (n = 486) was split randomly into two groups, sample 1 (n=150) used for exploratory factor analysis (EFA) and sample 2 (n=336) for confirmatory factor analysis (CFA). The data of second (n = 377) and third (n = 372) collection samples were used to perform test-retest reliability, internal consistency, and CFA of the SOQ-CA. The SOQ-CA obtained good reliability and validity through both EFA and CFA. The development of the SOQ-CA provides an opportunity to develop further theories and practices regarding the assessment of both sport motivation and individual achievement orientation. The application of the SOQ-CA in China would be significant for monitoring the development of adolescent physical activity and aiding in the implementation of policies.